Challenges and Perspectives of the Hybridization of PET with Functional MRI or Ultrasound for Neuroimaging. (15th October 2021) - Tournier, Nicolas; Comtat, Claude; Lebon, Vincent; Gennisson, Jean-Luc
Graphical abstract: Highlights: Hybridization of PET with fMRI or fUS raises technical/methodological challenges. Hybrid parameters that connect molecular and functional brain data can be obtained. fUS has a great potential to be hybridized with PET for preclinical neuroimaging. Abstract: Hybridization of positron emission tomography (PET) with other functional neuroimaging techniques such as functional magnetic resonance imaging (fMRI) or functional ultrasound (fUS) still raises technical and methodological challenges. Beyond the co-registration of anatomical images with functional data, development of hybrid imaging systems has paved the way for a large field of research based on the concept of bimodal functional neuroimaging such as PET/fMRI. In this framework, comparison of respective performances of brain PET and fUS suggests complementarity and great potential of hybrid PET/fUS for preclinical neuroimaging. Hybridization of functional neuroimaging techniques first offers opportunities to validate or improve measurement made by each modality. Future research may propose and validate hybrid parameters that quantitatively connect the brain molecular environment and the neuro-vascular coupling, which may improve our understanding of brain function in health and disease, with perspectives in neuroscience and neuropharmacology. In the coming years, cross-fertilization of neuroimaging communities and training of young researchers on multiple imaging modalities may foster the development of hybrid neuroimaging protocols that will take the full potential and the limitations of each modality into account.